Determinant factors of Yemeni maxillary arch dimensions - Nabil Muhsen Al-Zubair (Elsevier, 2015)
Objective: Information about maxillary arch and palatal dimensions in human populations is important for clinical orthodontics. This study was conducted to assess the determinants of maxillary arch dimensions in a sample of Yemeni individuals aged 18-25 years. Materials and Methods: The study sample comprised 214/765 adults (101 women, 113 men) who underwent clinical examination and fulfilled the study criteria. Study models were constructed and evaluated to measure maxillary arch and palatal dimensions. Results: The majority of mean maxillary arch dimensions were significantly greater in men than in women, with inter-second molar distance showing the greatest difference and palatal depth showing the least difference. Conclusion: Measurements of palatal depth and relationships of the canines to one another and to other teeth thus had the widest ranges, implying that these dimensions are the strongest determinants of maxillary arch size. Keywords: Maxillary arch dimensions, Arch length, Arch width, Yemeni norms